Upper Cretaceous Aeolian Depositional Systems: the Marilia Formation in the regions between Northwestern São Paulo and Southern Goiás (International Journal of Geoscience, Engineering and Technology, 2023)
This paper aimed at characterizing the sandstones and paleosols of the Marília Formation (Bauru Basin - upper Cretaceous), present in the southern region of Goiás and in the region of Marília (northwestern São Paulo), by means of petrographic analyses and field studies. Facies and architectural elements, compositional analyses of conglomerates and petrographic analyses of sandstones and paleosols were carried out, thus defining, and interpreting the depositional mechanisms. The Formação Marília, in the southern region of Goiás, is interpreted as an extensive eolic sand sheet, cut by ephemeral rivers, in which cyclic alternation between eolic deposits and paleosols occurs. The construction of the lithosomes was determined by different paleoclimatic conditions, responsible for moments with higher water availability, which favored the formation of soils, and others with lower water availability, favorable to the sedimentation of sandy deposits with eolian undulating marks. Three architectural elements were recognized: paleosols, sandy sheet deposits dominated by eolian wavy marks, and ephemeral river deposits. Paleosols are the most frequent elements and consist prevalently of Aridissols and subordinately of Alphissols. The sandstones were classified into lithoarenites (predominantly), sublithoarenites and feldspathic lithoarenites. The Marília Formation, in the Marília region, shows different development conditions in the lower and upper part of the Serra de Echaporã: in the lower part eolian sandstone deposits and ephemeral lakes alternate with paleosols indicating high water table and in the upper part eolian deposits and paleosols of arid and semiarid climate occur. Three architectural elements were recognized: paleosols, sand sheet deposits dominated by eolian wavy marks, and playa lake deposits. The paleosols consisted prevalently of Aridissols and subordinately of a gleying paleosol type. No ephemeral fluvial deposits were found.  The sandstones were classified into sublithoarenites and subarcosites (predominantly).  A construction model was proposed for this former sand sheet.  The construction phase was characterized by sediment input by rivers during a wetter period (first input), and by several cycles of erosion of ephemeral river deposits and soils during drier climatic phases (second input).